Travelogues of Turkiye in Urdu: Analysis and Index - Arzu CIFTSUREN (بازیافت)
As a literary genre travelogue is related to many branches of science. Although it is written from the perspective of its author, a travelogue certainly contains information in many fields from history to literature, daily life to cultural life, and politics to education. The tradition of writing travelogues in the Urdu language started with Yousuf Khan Kambalpush's Ajaibat-e Frang (1837). Travelogue writing has gained importance with the increase in travel to Europe and Islamic countries, due to various factors. Türkiye, undoubtedly, has a very important place in travelogues written in the Urdu language. Urdu travelogue of Türkiye, which was first written by Nawab Umar Ali Khan in 1885 under the name of “Aina-e Frang” was followed by some very important travelogues such as “Safarnam-e Rom u Misr u Sham” by Shibli Naumani, “Maqam-e Khilafat” by Shaikh Abdulqadir, “Bilad-e Islamiyya” by Abdurrahman Amritsari, “Safarnama-e Qustantiniya” by Hameedulah Khan Sarbuland Jang, “Duniya Aik Aurat ke Nazar main” by Akhtar Hamdiyya Bagum Sarbuland Jang,  “Safarnama-e Europe” by Munshi Mahboob Alam, “Sair-e Europe” by Nazli Rafia Sultan, “Sayahat-e Sultani” by Shah Banoo. More than a hundred travelogues of Türkiye have been written in Urdu from 1885 till the present. <span style="font-size: 12.0pt; line-height: 107%; font-family: "Times New Roman","serif"; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: TR; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">In this article, the travelogues on Türkiye written in the Urdu language will be examined and a bibliography of 100 Türkiye travelogues in Urdu will be listed